Selective homonuclear polarization transfer for spectroscopic imaging of GABA at 7T - Pan, JW (2012)
We develop and implement a selective homonuclear polarization transfer method for the detection of 3.0ppm C-4 GABA resonance by spectroscopic imaging in the human brain at 7T. This single shot method is demonstrated with simulations and phantoms, which achieves comparable efficiency of detection to that of J-difference editing. The macromolecule resonance that commonly co-edits with GABA is suppressed at 7T through use of a narrow band pre-acquisition suppression pulse. This technique is implemented in humans with an 8 channel transceiver array and high degree B(0) shimming to measure supplementary motor area and thalamic GABA in controls (n=8) and epilepsy patients (n=8 total). We find that the GABA/NAA (N-acetyl aspartate) ratio in the thalamus of control volunteers, well controlled and poorly controlled epilepsy patients are 0.053±0.012 (n=8), 0.090±0.012 (n=2), and 0.038±0.009 (n=6).